Current and future pharmacologic treatment of nonalcoholic steatohepatitis. Issue 3 (May 2017) - Banini, Bubu A.; Sanyal, Arun J.
Abstract : Purpose of review: Nonalcoholic steatohepatitis (NASH), the aggressive form of nonalcoholic fatty liver disease (NAFLD), can progress to cirrhosis and hepatocellular cancer in 5–15% of patients and is rapidly becoming the leading cause for end-stage liver disease. Dietary caloric restriction and exercise, currently the cornerstone of therapy for NAFLD, can be difficult to achieve and maintain, underscoring the dire need for pharmacotherapy. This review presents the agents currently used in managing NAFLD and their pharmacologic targets. It also provides an overview of NAFLD agents currently under development. Recent findings: Therapies for NASH can be broadly classified into agents that target the metabolic perturbations driving disease pathogenesis (such as insulin resistance and de novo lipogenesis) and agents that target downstream processes including cell stress, apoptosis, inflammation, and fibrosis. Modulation of peroxisome proliferator-activator receptors, farnesoid-X-receptors, and the glucagon-like peptide 1 pathway have been shown to improve liver histology. The intestinal microbiome and metabolic endotoxemia are novel targets that are currently under review. Antioxidants such as vitamin E, and more recently anti-inflammatory agents such as apoptosis signal-regulating kinase 1 inhibitors show promise as therapy for NASH. Several antifibrotic agents including cysteine-cysteine motif chemokine receptor type 2 and type 5 antagonists have been shown to inhibit the progression of fibrosis toward cirrhosis. Summary: There are currently several agents in the drug pipeline for NASH. Within the next few years, the availability of therapeutic options for NAFLD will hopefully curb the rising trend of NAFLD-related end stage liver disease.